Sepsis-associated thrombocytopenia. Issue 141 (May 2016) - Larkin, Caroline M.; Santos-Martinez, Maria-Jose; Ryan, Thomas; Radomski, Marek W.
Highlights: Incidence and significance of sepsis-associated thrombocytopenia (SAT). Analysis of studies examining potential mechanisms of SAT. Discussion of other causes of thrombocytopenia in ICU. Summary of ongoing research in this area.